Nutritional Value of Bitterballen Substitued with Pumpkin and Snakehead Fish as Alternative Protein-Source Snack for School-Age Children - Habibah, Nurina Umy; Naja Mayra, Dinar Annasta; Sekarsari, Alfina Nur; Putri, Rafita Retno (Journal of Food and Pharmaceutical Sciences, 2025)
Background: Protein-energy deficiency in school-age children is one of the problems caused by malnutrition in Indonesia. The potential local food ingredients can be used to prevent protein-energy deficiency. This research was conducted to determine the effect of substituting snakehead fish and pumpkin on the nutritional value of bitterballen. Method: This research is an experimental study. The substitution of pumpkin and snakehead fish was made using four formulas. The nutritional value of energy, protein, fat, and total carbohydrate was assessed to analyze the portion recommendation. Result: The energy content of raw bitterballen was increased, but decreased sequentially after cooking. The protein content of raw bitterballen was increased, however, in the fried bitterballen it was decreased sequentially. The fat content was increased drastically in all formulations after cooking. Total carbohydrate content was decreased both in the raw and fried bitterballen. Conclusion: In raw bitterballen, the energy content was higher in the substituted formula, mainly due to the increase in protein and fat from the addition of snakehead. The carbohydrate content decreased with adding pumpkin since it contains relatively low carbohydrates. The recommended portion for a snack is two pieces of fried bitterballen (50 g) per serving to meet the energy-protein needs of school-age children.